State-Induced Social Capital and Ethnic Integration: The Case of Rukun Tetangga in Penang, Malaysia - Azeem Fazwan Ahmad Farouk ,; Mohamad Zaini Abu Bakar , (Kajian Malaysia, 2007)
Proponents of social capital have argued that individuals bound together in dense social networks, infused with norms of reciprocity and trust, are better able and more inclined to act collectively for mutual benefit and social purposes as opposed to atomised individuals. This is due to the fact that the existence of social capital enables groups and individuals to deal smoothly and efficiently with various economic and social issues. Social capital is therefore seen as “sociological superglue” that holds society together. The social capital thesis, however, is based on studies done mainly in mature Western democracies where ethnic and racial cleavages do not figure prominently in the social structure. Questions such as what are the necessary requisites for social capital to flourish in a society that is divided along racial, ethnic, and religious lines and what are its repercussions (the existence or absence of social capital) have not been adequately addressed. Does the existence of social capital in such society have a moderating effect or will it polarise the society further? There is no doubt that norms of reciprocity and trust exist in all societies but do individuals in a highly polarised society trust other individuals from different ethnic or religious groups? In a modest attempt to address these issues, this article looks at the role of the state in generating social capital across racial, ethnic, and religious lines at the grass-roots level in the northern state of Penang, Malaysia. We argue that the creation of a “semi-autonomous” community organisations or a “state-induced social capital” plays a crucial role in fostering face-to-face interaction among individuals of different ethnic and religious lines in an otherwise a highly polarised society. This line of argument calls into question the social capital thesis which takes the existence of social capital as a given and cannot be generated by institutional conditions.